Terminação de cordeiros em confinamento com resíduo úmido de cervejaria como fonte de volumoso - Teixeira, William Soares (2018)
This study was conducted with the objective of evaluating the effect of increasing levels of wet brewery grain (WBG) as a source of bulk on nutrient intake, weight gain and economic viability, apparent nutrient digestibility, nitrogen and the ingestive behavior of lambs finished in feedlot. We used 32 male, uncastrated lambs, from single and double lambs, weaned with an average of 50 days of age and from continuous alternating crossbreeding between the Texel and Ile de France breeds. The diet was composed of bulky, this being the WBG, and by concentrate, composed of disintegrated corn, soybean meal, calcitic limestone and mineral salt. The treatments were constituted by four levels of WBG as dietary bulk (% of DM), being: 31, 44, 57 and 70%. Consumption of dry matter (DM), organic matter (OM), crude protein (CP) and total carbohydrate (TCH) in the various forms in which they were expressed were influenced in a quadratic manner by the increase of WBG inclusion in the diets. Ethereal extract (EE), neutral detergent fiber (NDF) and acid detergent fiber (ADF) intakes were linearly influenced while total digestible nutrient intakes (TDN) in a linearly decreasing manner. The average daily gain (ADG) was influenced in a quadratic manner, being at the maximum point of 0.375g, with a level of 46.9% WBG. Profitability was linearly increasing with the elevation of WBG levels. The coefficients of apparent digestibility of dry matter and organic matter showed a linear decreasing behavior. Excretions of fecal and urinary nitrogen and, consequently, of total nitrogen, were not significantly influenced (P>0.05) by the level of WBG. The amount of nitrogen retained in the animals' body decreased linearly (P≤0.05) with the increase of the WBG level as a bulky food of the diet. There was a linear increase (P<0.05) in the time and percentage of ingestion, rumination, and as a consequence, in the time and percentage of total chewing (feeding + rumination) with increasing WBG level in the diet, and reduction in the time spent for leisure. The use of the WBG as a source of feed of finished in confinement is a good alternative, even at the highest levels of the 70%, proving to be a food with good potential for use in finishing lambs in the feedlot system.